La propagande cachée sur les ondes de la BBC pendant la Seconde Guerre Mondiale : vers une héroïsation nationale - Cécile Vallée (Revue LISA)
With the aim of maintaining morale on the Home Front, as well as getting the British population to trust in final victory, the British government put in place a hidden control of the BBC, which was regularly instructed as to what broadcast form propaganda should take on the Home Service. These secret, regular and precise guidelines were to result in the projection of an ultra-positive image of Great Britain and of the British at war. The systematic hero-making propaganda was to become gradually better organised, more subtle, and therefore more efficient as the years went by thanks to the expertise of BBC staff. Countless programmes were broadcast, which stressed the heroic virtues of British soldiers, of the Navy and of the R.A.F, or reminded the listeners of past heroes, the glorious history of Great Britain being systematically commemorated, thus exalting national pride daily. To the constant cult of the heroes of the Home Front (particularly of women) corresponded an equally constant denigration of the Nazi enemy. Although there was no recourse to lies, the way both the military and the Home Front were presented was undoubtedly of a propaganda nature. Indeed, the aim was to win the hearts and minds of the British population by playing on two chords: on the one hand, turning the enemy into an evil beast, minimising defeats and difficulties, and, on the other hand, systematically extolling the power and glory of Great Britain and the innate qualities of the British.